EVALUASI KINERJA TERMINAL TIPE B SUNGAI KUNJANG KOTA SAMARINDA - WIJAYA, HARIYADI (KURVA S JURNAL MAHASISWA, 2014)
River Terminal Kunjang in Samarinda, is one of these terminals to accommodate large buses serving the route Samarinda-Balikpapan and buses currently serving the route Samarinda to several districts in Kutai upstream, such as Kota Bangun, Muara Kaman, Senoni , as well as to the West Kutai like Melak or Cape Isuy. But the condition is still visible inconvenience for users due to the lack of conformity of terminal facilities in accordance with the terms of a terminal. Performance River Terminal Kunjang looks not function properly due to lack of comfort facilities passengers and passengers prefer to not enter the terminal and wait in Jalan Fortunately Suropati for a ride to the bus they choose, this resulted in a delay in this road, because the wait passengers who got on the bus. Based on the results of the survey and analysis of the performance of the current Samarinda River Terminal, obtained;10,845 m2 land area, river terminal Kunjang samarinda meet the standards of the land area.±1. The location and footprint Kunjang River Terminal is located at coordinates 0 ° 31'45.82